Exploring ancient Greece - Yasuda, Anita (Mankato, MN 12 Story Library, 2018)
Examines the rise and fall of the ancient Greeks. Readers will come away with a comprehensive understanding of who the ancient Greeks were, how they built their empire, and what happened to their civilization.
The Minoan and Mycenaeans influenced ancient Greece -- The greeks created cities and colonies -- Sparta was powerful -- City-states held regular festivals -- Myths explained the world -- Athenians built the Parthenon -- Democracy began in Greece -- The Greeks loved to watch plays -- Greek philosophers figured things out -- Ancient greeks advanced science -- Wars divided Greece -- Ancient Greece changed the world.
Includes bibliographical references (page 31) and index.
Grade 4 to 6.
105796
Keywords: To 146 B.C.; Civilization; Greece -- Civilization -- To 146 B.C. -- Juvenile literature; Greece; Juvenile works